2020
DOI: 10.1038/s41598-020-64777-9
|View full text |Cite
|
Sign up to set email alerts
|

WFhb1-1 plays an important role in resistance against Fusarium head blight in wheat

Abstract: Fusarium head blight (FHB) is a severe disease of wheat (Triticum aestivum L.). Qfhb1 is the most important quantitative trait locus (QTL) for FHB resistance. We previously identified wheat gene WFhb1-1 (aka WFhb1-c1) as a candidate for FHB resistance gene. Here we report that WFhb1-1 has been cloned. The gene (GenBank # KU304333.1) consists of a single exon, encoding a putative membrane protein of 127 amino acids. WFhb1-1 protein produced in Pichia pastoris inhibits growth of both F. graminearum and P. pastor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
0
14
1
Order By: Relevance
“…In contrast, HRC was expressed in many genotypes with varying resistance levels, albeit to a much weaker extent in lines without the Fhb1 resistance allele. This expression pattern is inconsistent with the proposed susceptibility factor at HRC [9,87].…”
Section: Downstream Activation Of Plant Defense Mechanismcontrasting
confidence: 81%
See 2 more Smart Citations
“…In contrast, HRC was expressed in many genotypes with varying resistance levels, albeit to a much weaker extent in lines without the Fhb1 resistance allele. This expression pattern is inconsistent with the proposed susceptibility factor at HRC [9,87].…”
Section: Downstream Activation Of Plant Defense Mechanismcontrasting
confidence: 81%
“…However, the two studies disagreed on the mode of action being either the result of a recessive loss-of-function mutation [9] or a functionally novel allele actively conferring resistance [8]. Moreover, recently, Paudel et al [87] claimed that HRC acts as suppressor of WFhb1-1, which they suggested as the functional component of Fhb1. WFhb1-1 is located outside the QTL interval, but the deletion in HRC inactivates its suppression and results in the 'resistant HRC allele' [87].…”
Section: Host Defense Responses To Limit Fusarium Spreadmentioning
confidence: 99%
See 1 more Smart Citation
“…QTL regions were identified in RefSeqv1.0 based BLASTn analysis of markers Gwm133 and Gwm644 on chromosome arm 6BS for Fhb2 , ( Cuthbert et al, 2007 ), and Gwm304 and Gwm415 on chromosome arm 5AS for Fhb5 ( Xue et al, 2011 ). The Fhb1 genomic region was identified using sequences of candidate genes and gene containing contigs [ Fhb1-1 , GenBank accession KU304333.1 ( Paudel et al, 2020 ); PFT and PFT containing contig, GenBank accessions AY587018.1 and KX907434.1 ( Rawat et al, 2016 ); and TaHRC , GenBank accession MK450312.1 ( Su et al, 2019 )].…”
Section: Methodsmentioning
confidence: 99%
“…Although many determinants were already described as associated with wheat FHB resistance, the specific molecular mechanisms responsible for FHB resistance remain poorly understood (Wang et al, 2019), as exemplified by the QTL Fhb1 characterized as the most stable and efficient locus for wheat resistance to FHB (Bai et al, 1999;Ollier et al, 2020). While recent studies have shown that different mutations inducing the TaHRC gene loss of function explain part of this Fhb1-mediated resistance (Li et al, 2019;Su et al, 2019), further works have either suggested a role for the WFhb1-1 gene through its potential antifungal activity (Paudel et al, 2020) or for the TaLAC4 gene whose mutation leads to an increase of FHB susceptibility (Soni et al, 2020). In addition to the current sources of FHB resistance, several works introduced alternative forms of resistance via the identification of wheat genes involved in the success of the disease (reviewed in Fabre et al, 2020).…”
Section: Introductionmentioning
confidence: 99%